An anatomy of public sector unions - Barry T. Hirsch (Institute for the Study of Labor (IZA), 2013)
Public sector unionism grew rapidly during the late 1960s and early 1970s following the passage of state collective bargaining laws. During the last thirty years, public sector membership has grown at roughly the same rate as the overall workforce. This paper provides a descriptive overview of union membership growth and economy-wide employment shares in the U.S. federal (non-postal), Postal Service, state, and local government sectors. More limited evidence is provided on changes in relative public/private and union/nonunion wages. Observations are provided on the current debates regarding public/private pay and the role of public sector unions.
Keywords: J45; J5; 330; union membership; public sector unions; public sector pay; employment